THE TRANSFORMATIVE IMPACT OF WOMEN’S EMPOWERMENT IN THE VISION OF VIKSIT BHARAT 2047 - Trikoti, Sarita (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The vision of a developed India by 2047, often referred to as “Viksit Bharat,” is built on four central pillars—collectively termed ‘GYAN’: Garib (the underprivileged), Yuva (the youth), Annadata (farmers), and Nari (women). Among these, empowering women is crucial to realizing this national aspiration. Despite progress, India still faces entrenched structural challenges and social norms that limit women’s access to education and reduce their participation in the workforce. To overcome these barriers, focused efforts are needed to expand educational opportunities, improve access to healthcare, strengthen financial autonomy, and introduce effective policy measures that advance gender equality. Enhancing women’s roles in both the economy and governance can drive meaningful social and economic progress, resulting in higher productivity, resilient communities, and more representative institutions. By placing women’s empowerment at the center of its development strategy, India can accelerate its journey toward becoming a fair, inclusive, and prosperous nation by 2047.